2004
DOI: 10.1007/s00170-003-1647-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of ductile mode cutting in grooving of tungsten carbide with and without ultrasonic vibration assistance

Abstract: In this study, ductile mode chip formation in conventional cutting and ultrasonic vibration assisted cutting of tungsten carbide workpiece material has been investigated through experimental grooving tests using CBN tools on a CNC lathe. The experimental results show that as the depth of cut was increased there was a transition from ductile mode to brittle mode chip formation in grooving both with and without ultrasonic vibration assistance. However, the critical value of the depth of cut for ductile mode cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The critical DoC for ductile-brittle transition in machining of WC and glass using the ultrasonic vibration tool was found being much larger than that with the conventional stationary tool, which was increased to about 3.5 and 7 times, respectively [94,95]. A model was developed for brittle materials to predict the d c value for ultrasonic vibration cutting and experimental results well verified the predicted d c value, of which the d c value for DMC of silicon wafers was increased to around 2 times of that obtained without ultrasonic vibration assistance [97].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The critical DoC for ductile-brittle transition in machining of WC and glass using the ultrasonic vibration tool was found being much larger than that with the conventional stationary tool, which was increased to about 3.5 and 7 times, respectively [94,95]. A model was developed for brittle materials to predict the d c value for ultrasonic vibration cutting and experimental results well verified the predicted d c value, of which the d c value for DMC of silicon wafers was increased to around 2 times of that obtained without ultrasonic vibration assistance [97].…”
Section: Discussionmentioning
confidence: 82%
“…Some attempts have also been conducted on hybrid machining to help achieve ductile mode cutting [94][95][96][97][98][99][100][101][102]. The critical DoC for ductile-brittle transition in machining of WC and glass using the ultrasonic vibration tool was found being much larger than that with the conventional stationary tool, which was increased to about 3.5 and 7 times, respectively [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at a depth of cut of 1 lm, the force in the EVA cutting was 17 times lower than that in the conventional cutting in the cutting direction, 14 times lower in the thrust direction. Liu et al [10,119] found that there was a transition from ductile mode to brittle mode in both the conventional cutting and UVA cutting, but the critical depth of cut in UVA cutting was several times larger. In addition, the material removal ratio (the volume of material removal to the volume of the machined groove) in UVA grooving is close to 1, indicating a reduction on ploughing effect by the ultrasonic vibration.…”
Section: Sintered Alloysmentioning
confidence: 98%
“…27,28 This reflects that glass can also show plasticity under certain conditions. The scratch section in simulation is shown in Figure 5.…”
Section: Simulation Experiments Of Glass Scratchingmentioning
confidence: 99%